Something in the Air: Fetal air pollution exposure and long-run labour outcomes: Evidence from Germany. - Lidman,Johanna (2023)
This study examines the long-run impact of air pollution exposure at the month of birth and during pregnancy on labour outcomes in Germany. I match air pollution levels on a federal-state level to a longitudinal survey sample on individuals born in Germany. The study focuses on individuals born between 1985 to 1992, as this time period relates to consistent economic growth in Germany. The main identification strategy of this study is through sibling fixed effects. Thus, the impact of air pollution at birth on labour outcomes is identified by variation in pollution levels between siblings. Interestingly, the results of this study yield larger and more significant estimates using sibling fixed effects compared to the Ordinary Least Squares (OLS) method. The results show that carbon monoxide (CO) in the month of birth has a significant and adverse impact on real labour income in euros per month, actual work time per week and employment status at age 27. Furthermore, the burden of CO is carried by children of mothers with lower education levels in its entirety, highlighting the importance to minimise air pollution to reduce inequality in society. I also provide evidence that CO at birth has an adverse effect on cognitive ability in young adulthood. Average CO and O3 levels during the whole pregnancy or O3 at the month of birth do not have such a large impact on labour outcomes. These findings contribute to the existing literature by providing some of the first evidence on the long-term effects of CO exposure in-utero for a European country, corroborating the fetal origins hypothesis.
Keywords: Fetal origins hypothesis; Air pollution; Avoidance behavior; Human capital; Sibling comparisons